Management of hormonal therapy for the treatment of advanced hormone-dependent prostate cancer: A pharmacoeconomics assessment of the use of Degarelix – Firmagon® compared to generic triptorelin - Salinas Alva, Edgardo (2024)
Objective: This is a pharmacoeconomic evaluation of two therapy schedules using drugs with different modes of action: Degarelix and triptorelin in the treatment of patients with advanced hormone-dependent prostate cancer. Methods: We reviewed the literature on the standard treatment for these patients, early and late effects of existing therapies, and we also performed a valuation using the Comprehensive Cost Treatment EsSalud (Peruvian Social Security) rates. Results: The Comprehensive Cost Treatment is S/. 10 793 for a patient using Degarelix and S/. 12 251 for a patient using generic triptorelin, so the therapy with the GnRH antagonist generates S/. 1 458 savings per patient. Conclusions: This represents S/. 1,008,017 savings for all patients with advanced hormone-dependent prostate who attend to EsSalud, with the added advantage that there are no extra costs with the use of Degarelix because of the absence of complications due to any flare effect.